Visible-light-promoted organic dye-catalyzed sulfidation and phosphorylation of arylhydrazines toward aromatic sulfides and diarylphosphoryl hydrazides. (14th August 2019) - Li, Rui; Shi, Tao; Chen, Xiao-Lan; Lv, Qi-Yan; Zhang, Yin-Li; Peng, Yu-Yu; Qu, Ling-Bo; Yu, Bing
Abstract : Visible-light-promoted sulfidation and phosphorylation of arylhydrazines for the synthesis of aromatic sulfides and diarylphosphoryl hydrazides were developed using the organic dyes rose bengal and Na2 -eosin Y as photocatalysts, respectively. Abstract : Visible-light-promoted sulfidation and phosphorylation of arylhydrazines for the synthesis of aromatic sulfides and diarylphosphoryl hydrazides were developed using the organic dyes rose bengal and Na2 -eosin Y as photocatalysts, respectively. This strategy offers an efficient and mild transition-metal-free synthetic protocol for the formation of C–S and N–P bonds from arylhydrazines.